2004
DOI: 10.1039/b414545c
|View full text |Cite
|
Sign up to set email alerts
|

Deuteration effects on the vibronic structure of the fluorescence spectra and the internal conversion rates of triangular [4]phenylene

Abstract: Deuteration effects on the vibronic structure of the fluorescence spectra and the internal conversion rates of triangular [4]Phenylene U n i v e r s i t ä t P o t s d a m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Mixed isomers that contain linear and angular structural units are also known. , These [ N ]­phenylenes have been prepared by Vollhardt and co-workers via a convenient [2 + 2 + 2] cycloaddition reaction using CpCo­(CO) 2 as the catalyst. The geometry, aromaticity, and properties of [ N ]­phenylenes have been reported based on both experimental ,, and theoretical approaches. These studies have revealed that the aromaticity and E Gap of [ N ]­phenylenes are influenced by the number and position of annulated benzocyclobutadieno moieties on the central 6MRs. For instance, the anti-aromatic character of four-membered rings in [ N ]­phenylenes decreases in the following order: linear [3]­phenylene, angular [3]­phenylene, and branched [4]­phenylene, leading to overall E Gap enlargement …”
Section: Introductionmentioning
confidence: 99%
“…Mixed isomers that contain linear and angular structural units are also known. , These [ N ]­phenylenes have been prepared by Vollhardt and co-workers via a convenient [2 + 2 + 2] cycloaddition reaction using CpCo­(CO) 2 as the catalyst. The geometry, aromaticity, and properties of [ N ]­phenylenes have been reported based on both experimental ,, and theoretical approaches. These studies have revealed that the aromaticity and E Gap of [ N ]­phenylenes are influenced by the number and position of annulated benzocyclobutadieno moieties on the central 6MRs. For instance, the anti-aromatic character of four-membered rings in [ N ]­phenylenes decreases in the following order: linear [3]­phenylene, angular [3]­phenylene, and branched [4]­phenylene, leading to overall E Gap enlargement …”
Section: Introductionmentioning
confidence: 99%
“…Conjugated ladder polymers have attracted intense attention because of their intriguing properties, which are distinct from those of conventional conjugated polymers. As a result of their fully conjugated and rigid polymer backbones, conjugated ladder polymers possess some intriguing properties, including high charge carrier mobilities, , long exciton diffusion lengths, and low energy gaps. ,, Ladder phenylenes (LPs) represent a unique family of conjugated ladder polymers, comprising one-dimensional ladder chains of linearly alternating fused benzene and cyclobutadiene rings. , Because of the unusual combination of aromatic and antiaromatic moieties, LPs are expected to possess unique optical and electronic properties and are considered promising materials for applications in optoelectronic devices. Ever since the pioneering synthesis of biphenylene by Hosaeus, many efforts have been made to synthesize LP chains. ,, To date, the longest prepared LPs have contained five benzene units, , and the synthesis of longer, polymeric LPs remains a great challenge. Moreover, experimental investigation of the properties of existing LPs has been limited to collecting the average signals of ensembles of LP molecules. , Thus, the synthesis and characterization of individual LPs have not been achieved, which severely hampered the exploration of the properties of these unusual conjugated ladder polymers.…”
mentioning
confidence: 99%
“…All frequencies are unscaled. DFT, in particular B3LYP, has shown to provide accurate geometries and good harmonic vibrational frequencies for a broad range of molecules and ions [48][49][50]. As shown recently, the level of theory selected is well suited for nuclear magnetic resonance [51,52] and NICS calculations [53][54][55][56].…”
Section: Methodsmentioning
confidence: 99%